2004
DOI: 10.30843/nzpp.2004.57.6913
|View full text |Cite
|
Sign up to set email alerts
|

Emergence sexual maturation and oviposition of <i>Aphidius ervi</i> (Hymenoptera Aphidiidae)

Abstract: Aphidius ervi Haliday is an important parasitoid of several aphid species and information is needed for the development of massrearing techniques and better understanding of biological control ecology The emergence sexual maturation and oviposition of A ervi on pea aphid Acyrthosiphon pisum (Harris) was studied in the laboratory at 201deg;C and 6070 RH with 168 h lightdark About 95 of parasitoids emerged during the photophase Females needed a significantly longer time than males to complete their life cycle Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Emergence of D. rapae was triggered by light and prevented by darkness. Emergence of parasitoids at the start of photophase has also been observed in other species, such as Bathyplectes curculionis, Exorista japonica and Aphidius ervi (England 1995;Nakamura 1997;He et al 2004). The emergence of D. rapae during early photophase gives them more time and opportunity for finding suitable mates and hosts.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Emergence of D. rapae was triggered by light and prevented by darkness. Emergence of parasitoids at the start of photophase has also been observed in other species, such as Bathyplectes curculionis, Exorista japonica and Aphidius ervi (England 1995;Nakamura 1997;He et al 2004). The emergence of D. rapae during early photophase gives them more time and opportunity for finding suitable mates and hosts.…”
Section: Discussionmentioning
confidence: 63%
“…Some parasitoids are active during early photophase (England 1995;Nakamura 1997) while others are active in late photophase (Allen 1998). To understand the reproductive strategies of parasitoids, it is important to know their emergence, mating and oviposition patterns (He et al 2004). Parasitoids may also synchronise the timing of their emergence in order to increase their chances of mating and oviposition, which will ultimately maximise reproductive fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Sharp drops in duration of daylight also stimulated oviposition by Pyralidae at dusk (Tshernyshev, 1984). He et al (2004) reported that about 95% of Aphidius ervi Haliday, an important parasitoid of aphids, emerged during the photophase. Females attacked aphids in both light and dark conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the higher paternal half-sibs between than within parasitoid populations, several interacting factors could contribute to a greater dispersion of A. ervi males between populations. (1) A male-biased sex ratio (Clobert et al 2001;Ronce 2007;Nelson and Greeff 2011), though sex ratio is commonly female-biased in most aphid parasitoid species (Mackauer 1976;Sequeira and Mackauer 1993); (2) A local mate competition between males (Nelson and Greeff 2011; Greeff et al 2003;Henry 2008), which has already been described for Aphidius parasitoids (Godfray 1994); (3) A reproductive strategy resulting in monogamous mating for A. ervi females and polygamous males (Godfray 1994;He and Wang 2008); (4) The existence of philopatry in female parasitoids (Johnstone et al 2012) or host fidelity in females of A. ervi (Zepeda-Paulo et al 2013); and (5) the occurrence of protandry, in which male parasitoids emerge from their mummies before female parasitoids, a phenomenon described for several parasitoid species including A. ervi (Godfray 1994;He et al 2004). Therefore, males should be more likely to leave the natal host patch looking for suitable mates elsewhere when females and/or virgin females are absent, which is common when females exhibit a monogamous behavior (Martel et al 2008).…”
Section: Differential Dispersal Of Parasitoid Females and Malesmentioning
confidence: 99%